2019
DOI: 10.1038/s41418-019-0370-1
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 promotes the targeting and clearance of necroptotic cells

Abstract: Inflammation-resolution is a protective response that is mediated by specialized pro-resolving mediators (SPMs). The clearance of dead cells or efferocytosis is a critical cellular program of inflammation-resolution. Impaired efferocytosis can lead to tissue damage in prevalent human diseases, like atherosclerosis. Therefore understanding mechanisms associated with swift clearance of dead cells is of utmost clinical importance. Recently, the accumulation of necroptotic cells (NCs) was observed in human plaques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 43 publications
(68 reference statements)
2
110
0
Order By: Relevance
“…Hepatocellular carcinoma ensues in the presence of excessive hepatic apoptosis and necroptosis in the tumor microenvironment which directs lineage commitment to either hepatocellular carcinoma or intrahepatic cholangiocarcinoma ( Seehawer et al, 2018 ). The clearance of necroptotic cells are inefficiently taken up by macrophages in diseases characterized by impaired inflammation resolution ( Gerlach et al, 2020 ) . Necroptotic cells are inefficiently taken up by macrophages because they have increased surface expression of CD47, a “don't eat me” signal ( Gerlach et al, 2020 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma ensues in the presence of excessive hepatic apoptosis and necroptosis in the tumor microenvironment which directs lineage commitment to either hepatocellular carcinoma or intrahepatic cholangiocarcinoma ( Seehawer et al, 2018 ). The clearance of necroptotic cells are inefficiently taken up by macrophages in diseases characterized by impaired inflammation resolution ( Gerlach et al, 2020 ) . Necroptotic cells are inefficiently taken up by macrophages because they have increased surface expression of CD47, a “don't eat me” signal ( Gerlach et al, 2020 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…The clearance of necroptotic cells are inefficiently taken up by macrophages in diseases characterized by impaired inflammation resolution ( Gerlach et al, 2020 ) . Necroptotic cells are inefficiently taken up by macrophages because they have increased surface expression of CD47, a “don't eat me” signal ( Gerlach et al, 2020 ). Resolvin D1 enhanced the clearance of necroptotic cells in advanced murine plaques by the release of the “eat me signal” calreticulin from macrophages in a CDC42 dependent manner ( Gerlach et al, 2020 ) .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…A body of evidences showed that CALR is highly expressed in tumor cells and transported onto cell membrane to serve as a C1q receptor and prophagocytic signal for macrophage phagocytosis of cancer cells and dead cells (12,13). Because the exposed CALR can be released into extracellular milieu (14,15), the serum CALR is highly elevated in the tumor patients and positively correlated to the prognosis of tumor (16,17). Therefore, serum CALR is considered as a useful biomarker in cancer diagnosis and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the critical evidence supporting exposure of surface calreticulin (CALR) by necroptotic cells is largely absent. Moreover, CD47, a well-known "do not eat me" signal, has been found to modulate phagocytic clearance of necroptotic cells [157,159]. Irrespective of these observations, it is generally accepted that the uptake of necroptotic cells might not be as proficient as that of apoptotic cells [156][157][158][159], although an opposite scenario in which necroptotic cells were efferocytosed more efficiently, has also been proposed [137].…”
Section: Necroptosis: Innate Immune Attraction and Phagocytic Clearancementioning
confidence: 99%